Morphological differences of elite Croatian soccer players according to the team position - Matkovic, B. R.; Micigoj-Durakovic, M.; Matkovic, B.; Jankovic, S.; Ruzic, L.; Leko, G.; Kondric, M. (Collegium Antropologicum, 2003)
Team position is of extreme importance in interpretation of morphological data because there are specific demands for a specific play position. The aim of the study was the analysis of morphological characteristics and body composition of elite Croatian soccer players with respect to their team position. The measurements were performed on 57 soccer players, members of the First Croatian National League. The anthropometrical measurement encompassed 13 variables. Descriptive statistics, t-test and MANOVA were used in data processing. The goalkeepers were the tallest and the heaviest (182.9 4.3 cm; 80.1 5.1 kg), and had significantly higher amounts of body fat (20.2% goalkeepers vs. 13-15% others; p<0.05), whereas the forwards and the midfield players were on the average about 3 cm shorter. The goalkeepers had longer legs and arms (p<0.05), and the largest biacromial diameter (43.2 1.9 cm). The forwards were the shortest on the average (179.2 6.3 cm). The lowest values of fat tissue were found in defenders (13.9%) and midfield players (14.4%). In conclusion, the differences in morphological characteristics according to the team position were noticed only in goalkeepers, especially regarding their height, weight and the percentage of fat tissue.